The Influence of Pay Satisfaction, Job Satisfaction, Competence, and Turnover Intention on the Service Quality of Honorary Employees in the Airport Operational Unit Office of Class III North Kalimantan - Asnoni, Asnoni; Sambung, Roby; Milwan, Milwan (LPPM Universitas Terbuka, 2021)
The study aims to determine the effect of pay satisfaction, employee job satisfaction, and competence on turnover intention and its impact on the service quality of honorary employees. The research method is quantitative research by the survey through questionnaires. The research sample was honorary employees in the Airport Operational Unit Office of Class III Kol. RA. Bessing Malinau, Tanjung Harapan, and Nunukan who have worked for more than 1 (one) year as many as 85 employees. The sampling technique in this study is a proportionate stratified random sampling technique. This research was conducted in September 2019 to February 2020. Data were analyzed using SEM PLS analysis. The results showed that pay satisfaction and job satisfaction had a significant and positive effect on service quality. Pay satisfaction, job satisfaction, and competence had a significant and negative effect on turnover intention. The turnover intention had a significant and negative effect on service quality. Pay satisfaction had a significant and indirect positive effect on service quality through turnover intention. Job satisfaction and competence did not have a significant indirect effect on service quality through turnover intention. Evaluation of employee satisfaction and competence in the organization is important to be carried out regularly. The most important thing is that this research will contribute to the body of knowledge, especially in human resource management science.